(untitled) (The Review of Diabetic Studies, 2025)
Traumatic hemorrhage remains a leading cause of preventable death worldwide. Early hemostatic intervention is critical in reducing mortality, particularly before hospital arrival. Tranexamic acid (TXA), an antifibrinolytic agent, has gained increasing attention for its role in controlling bleeding in prehospital trauma care. This systematic review evaluates the effectiveness of prehospital TXA administration in trauma patients with suspected hemorrhage. Literature published between 2010 and 2025 was retrieved from PubMed, Scopus, and Web of Science using PRISMA guidelines. Studies assessing mortality reduction, transfusion requirements, and adverse events following TXA administration in prehospital settings were included. The results indicate a consistent association between early TXA administration and improved survival, particularly when given within three hours post-injury. TXA also reduced blood transfusion requirements without significantly increasing thromboembolic events. However, variation in dosing protocols and patient selection criteria highlights the need for standardized prehospital guidelines. The review concludes that prehospital TXA administration is an effective, safe, and feasible strategy to improve outcomes in trauma-induced hemorrhage, emphasizing the importance of training and early recognition of bleeding severity.